Synthesis of click‐reactive HPMA copolymers using RAFT polymerization for drug delivery applications. Issue 23 (30th September 2013) - Ebbesen, Morten F.; Schaffert, David H.; Crowley, Michael L.; Oupický, David; Howard, Kenneth A.
ABSTRACT This study describes a versatile strategy combining reversible addition fragmentation transfer (RAFT) polymerization and click chemistry to synthesize well‐defined, reactive copolymers of N‐(2‐hydroxypropyl)methacrylamide (HPMA) for drug delivery applications. A novel azide containing monomer N‐(3‐azidopropyl)methacrylamide (AzMA) was synthesized and copolymerized with HPMA using RAFT polymerization to provide p(HPMA‐co‐AzMA) copolymers with high control of molecular weight (∼10–54 kDa) and polydispersity (≤1.06). The utility of the side‐chain azide functionality by Cu(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC) was demonstrated by efficient conjugation (up to 92%) of phosphocholine, a near infrared dye, and poly(ethylene glycol) (PEG) with different substitution degrees, either alone or in combination. This study introduces a novel and versatile method to synthesize well‐defined click‐reactive HPMA copolymers for preparing a panel of bioconjugates with different functionalities needed to systemically evaluate and tune the biological performance of polymer‐based drug delivery. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 5091–5099